(untitled) (Research, Society and Development, 2024)
The article aims to analyze the relationship between vaccination coverage of the MeningoC vaccine and confirmed cases of meningitis in Maceió – AL, from 2018 to 2022, in children up to 9 years of age. This is cross-sectional ecological research, characterized by a descriptive approach of a quantitative nature, using data from DATASUS, using systems such as SI-PNI, SIH-SUS, and SINAN. A retrospective collection and bibliographic review were carried out with SciELO and MEDLINE. Tabulation and analysis were done using Microsoft Office Word and Excel. The transversal nature does not require ethical evaluation by the Research Ethics Committee and the ICF. Herd immunity occurs when a high proportion of the population is immune, minimizing disease spread. Vaccination in the PNI reduced serious cases in Brazil, but low adherence has increased cases in Maceió-AL. The effectiveness of immunization and vaccination coverage needs to be evaluated, and awareness and public health measures are essential to reduce the incidence and ensure a healthier environment for children. To reverse the situation in Maceió-AL, it is important to intensify vaccination, improve the tests, and guarantee the documentation of chemoprophylaxis. Mass immunization, strengthening epidemiological surveillance, and laboratory capabilities are crucial to controlling the disease. Collaboration between state and local authorities is vital to prevent future outbreaks of meningococcal meningitis.